2012
DOI: 10.1075/target.24.1.04shl
|View full text |Cite
|
Sign up to set email alerts
|

More spoken or more translated?

Abstract: Since the early 1990s, with the advance of computerized corpora, translation scholars have been using corpus-based methodologies to look into the possible existence of overriding patterns (tentatively described as universals or as laws) in translated texts. The application of such methodologies to interpreted texts has been much slower in developing than in the case of translated ones, but significant progress has been made in recent years. After presenting the fundamental methodological hurdles -and advantage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…In general, the interpretations seem to exhibit features of spoken language, though "it may also be argued that interpreted discourse displays features which set it apart; i.e., features of interpretese" (Shlesinger 2008, p. 250). Shlesinger and Ordan (2012) provide additional corpus evidence confirming that interpreted language exhibits features of spoken language. Pronouns and adverbs are more frequent in simultaneous interpretations than in written translation.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…In general, the interpretations seem to exhibit features of spoken language, though "it may also be argued that interpreted discourse displays features which set it apart; i.e., features of interpretese" (Shlesinger 2008, p. 250). Shlesinger and Ordan (2012) provide additional corpus evidence confirming that interpreted language exhibits features of spoken language. Pronouns and adverbs are more frequent in simultaneous interpretations than in written translation.…”
Section: Introductionmentioning
confidence: 55%
“…Pronouns and adverbs are more frequent in simultaneous interpretations than in written translation. Moreover, Shlesinger and Ordan (2012) show that proper nouns are severely underrepresented in simultaneous interpretations, which is interpreted as reflecting the oral nature of interpreting.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several studies have been done on spoken language interpreters that identified the explicitation of various aspects of a target text. Shlesinger (1995) found evidence of shifts in cohesion between English and Hebrew and in a later study again looking at interpreters working from English to Hebrew, Shlesinger and Ordan (2012) found an increased use of adverbs in their target texts. Gumul (2006) noted an increase in conjunctive devices in the work of interpreters between English and Polish, as did Becher (2011) in a corpus study of English to German translations.…”
Section: Introductionmentioning
confidence: 87%
“…Due to their statistical character, these properties can be automatically uncovered (Baroni and Bernardini, 2005;Volansky et al, 2015;Kunilovskaya and Lapshinova-Koltunski, 2020) and have recently received increased attention in multilingual language processing (Dutta Chowdhury et al, 2020;Artetxe et al, 2020;Graham et al, 2020). However, simultaneous interpreting as a spoken mediation type tends to show different properties than translation (Kajzer-Wietrzny, 2012), interpretese being more pronounced overall and reinforcing spoken features (Shlesinger and Ordan, 2012).…”
Section: Translation and Interpreting Studiesmentioning
confidence: 99%